The Impact of Rebranding on University Brand Equity - Yudis Puspitasari, Aditia; MS, Mahrinasari; Rouly H. Pandjaitan, Dorothy (International Journal of Scientific Research and Management (IJSRM), 2022)
Universities are required to be different from competitors and attract more students. One of the strategies undertaken is rebranding to build stronger brand equity. This research was conducted at a private university in Indonesia to determine the effect of rebranding on brand equity and to analyze differences in brand equity before and after rebranding. This study uses a quantitative approach. The dimensions of university brand equity are brand awareness, perceived quality, brand association, and brand loyalty. Data were collected using a questionnaire survey of students, lecturers, and employees with a total of 268 respondents. Quantitative analysis shows that rebranding has an effect on university brand equity with a low coefficient of determination. The results of the different t-test showed that there was no difference in brand equity before and after the rebranding. From these results, it can be concluded that the brand equity of the old brand was successfully transferred to the new brand with a shift in perception of the dimensions of brand equity. The success of the transfer of brand equity is because the institution respects the history of each of the origin universities. In addition, increasing reputation from high school to university is also one of the strong reasons for the success of brand equity transfer, especially when it is associated with brand awareness, brand association, and perceived quality. This study supports the results of previous studies by Marques et al. (2020) and Beise-Zee (2022).